The quantity of neutrofil and makrophage after the application of red ginger on white rats with chronic periodontitis - Andayani, Ridha; Chismirina, Santi; Pratiwi, Hessyi Amanda; Husni, Melati Hayatul (Universitas Padjadjaran, 2016)
Introduction: Chronic periodontitis is the most common form of periodontitis. The major etiology of periodontitis is gram-negative anaerobic bacteria, such as Aggregatibacter actinomycetemcomitans, Treponema denticola, Tannarela forsythia and Porphyromonas gingivalis which locally invade periodontal tissues and affect the immune system cells. Neutrophils and macrophage play central role in inflammation. The objective of this study was to evaluate the quantity of neutrophil and macrophage due to the application of red ginger (Zingiber officinale var rubrum) extract of rat chronic periodontitis. Methods: The type of this research was experimental laboratoris post test only control group. In order to induce experimental periodontitis, the mandibular insisivus was assigned to receive wire 0,008 inch in marginal gingival. Then, red ginger (Zingiber officinale var rubrum) extract that has bioactive compounds was topically administered to the rats. Results: This study showed there were no neutrophils in histopathologic of rat’s periodontal tissue, bu there were amount of macrophage. Then macrophage analyzed by one way ANOVA showed significant differrences in each group (P<0,05) and continued with LSD. Conclusions: there was no effect of red ginger (Zingiber officinale var rubrum) extract toward the quantity of neutrophils, but affected on the number of macrophage.